(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
The development of dialogical speech of preschool children is an important and complex topic in modern preschool pedagogy. It is at preschool age that speech is actively developing, prerequisites for further interpersonal communication of the child are being formed, vocabulary is accumulating, activity in word-making is being brought up, and at the same time the foundations of correct pronunciation of words and spelling, the foundations of speech culture are being laid.